PENYELESAIAN TERHADAP KASUS SERTIPIKAT GANDA OLEH BADAN PERTANAHAN NASIONAL - Zathira, Zahra (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
The main material of the research is Completion Of The Double Certificate Case By The National Land Agency with the following problem formulation: 1. How did the emergence of a double certificate which constitutes legal evidence of land ownership?2. How is the resolution carried out by the authorities in resolving the issue of dual certificates? From the results of the study concluded the following conclusions: 1. The cause of the double certificate could be due to the element of intent, accidental and due to administrative errors. The emergence of a double certificate is also caused by the lack of discipline and order of government officials related to the land sector in carrying out their duties. 2. The National Land Agency is not a state institution in the field of judiciary, but nevertheless the National Land Agency has the authority to resolve any land issues including the issue of dual certificates. This authority is only limited to administrative authority, namely the cancellation or revocation of a certificate issued by the National Land Agency itself. The National Land Agency always strives for solutions to resolve land disputes based on the prevailing laws and regulations with due regard for a sense of justice and respect for the rights and obligations of each party. is deliberation. The steps for resolving disputes that they or the National Land Agency take in a dual certificate dispute are negotiation, mediation and facilitation.